Production of α-Amylase by Aspergillus terreus NCFT 4269.10 Using Pearl Millet and Its Structural Characterization - Sethi, Bijay K.; Jana, Arijit; Nanda, Prativa K.; DasMohapatra, Pradeep K.; Sahoo, Santi L.; Patra, Jayanta Kumar (Frontiers in Plant Science, 2016)
In this investigation, Aspergillus terreus NCFT4269.10 was employed in liquid static surface (LSSF) and solid state (SSF) fermentation to assess the optimal conditions for α-amylase biosynthesis. One-variable-at-a-time approach (quasi-optimum protocol) was primarily used to investigate the effect of each parameter on production of amylase. The maximum amylase production was achieved using pearl millet (PM) as substrate by SSF (19.19± 0.9 Ug-1) and also in presence of 1mM magnesium sulphate, 0.025% (w/v) gibberellic acid and 30 mg/100ml (w/v) of vitamin E (~ 60 fold higher production of amylase) with the initial medium pH of 7.0 and incubation at 30 ºC for 96 h. In addition, maltose, gelatin and isoleucine also influenced the α-amylase production. Amylase was purified to homogeneity with molecular mass around 15.3 kDa. The enzyme comprised of a typical secondary structure containing α-helix (12.2%), β-pleated sheet (23.6%) and β-turn (27.4%). Exploitation of PM for α-amylase production with better downstream makes it the unique enzyme for various biotechnological applications.